A Social Trap Analysis of the Management of Diversity - Barry, Bruce; Bateman, Thomas S. (Academy of Management Review, 1996)
Social trap theory is the basis for an analysis of how management initiatives influence diversity-related outcomes within work organizations. Social traps are situations where decision problems involve conflicts between individual or near-term outcomes and collective or long-term consequences. The management of diversity is conceptualized in terms of the social traps created by workplace diversity issues. A social trap model is proposed that (a) identifies the defining attributes of social traps in diversity contexts, (b) links human resource initiatives with a taxonomy of social trap solutions, (c) explores the efficacy of these solutions for altering the dynamics of social traps, and (d) examines the influence of changes in trap dynamics on an organization's diversity climate. We discuss the contribution and implications of a social trap approach to diversity and outline a research agenda for the model.